A snapshot of bacterial endophytes isolated from the roots of Vetiver grass (Chrysopogon zizanioides) grown at Bien Hoa airbase, Dong Nai province - Vu, Thi Lan Anh; Nguyen, Thi Nhan; Dang, Thi Ha Thu; Pham, The Hai; Nguyen, Quoc Dinh; Ngo, Thi Thuy Huong; Tran, Van Tuan (Vietnam Journal of Science and Technology, 2024)
Vetiver grass (Chrysopogon zizanioides) is used for phytoremediation of contaminated soil, but the role of its associated endophytic bacteria remains unexplored. This study investigated endophytic bacteria from Vetiver grass grown in dioxin-contaminated soil at Bien Hoa airbase, Vietnam. Sixteen bacterial strains were isolated and identified using 16S rRNA gene sequencing, revealing nine distinct species. Notably, four strains (Klebsiella variicola B1, Enterobacter cloacae B4, B6, and Enterobacter asburiae B11) exhibited high indole acetic acid (IAA) production, a plant growth hormone. Strains K. variicola B1 and E. cloacae B4 also displayed phytase and phosphatase activity, potentially enhancing plant nutrient availability. These IAA-producing strains were further evaluated for their ability to promote tomato plant growth. After 28 days of root inoculation, tomato plants exhibited a 19-22% increase in growth compared to controls. This study highlights the first isolation of endophytic bacteria from Vetiver grass in dioxin-contaminated soil and identifies potential bacterial candidates for plant growth promotion in such environments.